(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2023)
Chance, regularly introduced in the artistic practice through dada and surrealist experimentations, gets studied again by many artists during the second half of the 20th century. In this context, one of the most important figures is John Cage: his arrival in 1959 in Italy represents an important step for all the further analysis about randomness and more. In 1961 Umberto Eco writes La forma del disordine, published in Almanacco Letterario Bompiani 1962: the essay explains and sheds light on the connections between art, science and chance, while showing some photographic reproductions of kinetic and programmed artworks, in which Bruno Munari’s Struttura continua N. 018 and Davide Boriani’s Immagini ottenute sostituendo ai numeri i quadrati stand out. The first one is composed of modular, metallic elements, which can be assembled thanks to a connecting system, obtaining an infinite number of different compositions. The second one is based on a permutation process from number to graphic sign, which is already explicated by the title. Between 1972 and 1974, Grazia Varisco puts chance and permutation together in Random walks by random numbers, a series of five silk-screen prints. Associating a colour and a shape of her choice to random numbers – used in mathematical statistics – the artist obtains five different, bidimensional, abstract geometrical graphic compositions. All three works are different from each other, nonetheless they are somehow connected from an experimental point of view.